ПРОБЛЕМА ЛЕКСИКОГРАФИЧЕСКОГО ОПИСАНИЯ МЕЖДОМЕТИЙ (Philological Studies, 2019)
The modern lexicography is aimed at making active type dictionaries, which «portray» a lexeme demonstrating its functions in different aspects. The main difficulties in the lexicographical fixation are connected with so-called discursive words, which have «fuzzy» semantics and a wide scope of use. There are also interjections and onomatopoeia among lexemes. The paper deals with the principles of making an interjections and onomatopoeia dictionary using the Macedonian language material. There are samples of vocabulary entries in the annex.
Keywords: interjection, onomatopoeia, dictionary, vocabulary entry, Macedonian language